Effect of organizational identification on organizational commitment among primary Omani schools : Empirical study - Alshuhumi, Said Rashid Ali; Al-Hidabi, Dawood Abdulmalek Yahya; Aldaba, Abdulmajid Mohammed Abdlwahab (Journal of Educational and Psychological Sciences, 2021)
The current research amid to examine the effect of organizational identification on organizational commitment of the primary school teachers, Sultanate of Oman. The researchers adopted the descriptive survey method which is the appropriate approach that suits the objectives of this study. Based on the nature of this quantitative study, the researcher used the The results from the descriptive analysis revealed high level of The results from structural equation modeling showed a direct impact of organizational identification on organizational commitment, Where the size of the effect cIn addition, teachers qualification diploma - bachelor and master sowever no moderating effect was found for both teachers’ gender and years of experience in this relationship. The research included a number of recommendations, including supporting the teachers financially and emotionally, creating the conducive learning environment by providing the requirements of the educational process. The current research also recommended supporting the professional development and scientific scholarship as well as the participation in various educational activities. Finally, this study recommended granting the teachers special privileges from both government and private sector as well as enhancing their social status.
Keywords: Organizational Commitment; Basic Education; Sultanate of Oman; Effect; organizational identification; primary Omani schools